LANGUAGE SHIFT FROM SUNDANESE LANGUAGE TO INDONESIAN LANGUAGE - Topan Sopyan; Gartika Pandu Bhuana (PROJECT (Professional Journal of English Education), 2022)
Language is not merely a system of communication. It represents culture and transmits culture from one generation to the next. This study aims to determine  the language pattern as well as the students’ attitude to the shift of Sundanese language to Indonesia language. The methodology  was qualitative. The results of analysis showed that students usually use Sundanese language to communicate with their parents, family, closest friend, and the older people. However, they prefers to use Indonesia language while doing a conversation in education field, especially with the lecture. Regarding attitude, most of the students had positive attitude in maintaining Sundanese language. Regrettably, as most of them do interaction in urban area, they thought that speaking Sundanese seemed out of date. Keywords:  Sundanese Language, Language Shift, Language Maintenance